MicroRNA-29a promotes the proliferation of human nasal epithelial cells and inhibits their apoptosis and promotes the development of allergic rhinitis by down-regulating FOS expression. - Yuqin Fan (Public Library of Science (PLoS), 2021)
Objective To explore the regulation of microRNA-29a (miR-29a) on FOS in human nasal epithelial cells and its molecular mechanism, as well as the effects of miR-29a on the cell proliferation and apoptosis. Methods By cell transfection, gene silencing, quantitative real-time polymerase chain reaction (qRT-PCR), flow cytometry and TUNEL assay (for cell apoptosis), CCK-8 assay (for cell proliferation), dual-luciferase reporter gene assay and Western Blot, it was validated that miR-29a promoted the proliferation of human nasal epithelial cells and inhibited their apoptosis by down-regulating FOS expression in RPMI2650 and HNEpC cell lines. Results ①Compared with healthy controls, miR-29a expression was up-regulated and FOS mRNA expression was down-regulated in the nasal tissues from the patients with allergic rhinitis (AR). ②MiR-29a over-expression promoted the proliferation of RPMI2650 cells and HNEpC cells but inhibited their apoptosis. ③MiR-29a targeted at FOS. ④MiR-29a over-expression and FOS silencing both significantly promoted cell proliferation and inhibited cell apoptosis. After transfection with both miR-29a and FOS, there was a decrease in the proliferation but an increase in the apoptosis of cells.⑤MiR-29a promoted the proliferation of human nasal epithelial cells and inhibited their apoptosis by down-regulating FOS expression. Conclusion MiR-29a-/FOS axis can be regarded as a potential marker and a new therapy for AR.